Advances in Therapeutic Fc Engineering – Modulation of IgG-Associated Effector Functions and Serum Half-life - Saxena, Abhishek; Wu, Donghui (Frontiers in Immunology, 2016)
Today monoclonal immunoglobulin gamma (IgG) antibodies have become a major option in cancer therapy especially for the patients with advanced or metastatic cancers. Efficacy of monoclonal antibodies (mAbs) are achieved through both its antigen binding fragment (Fab) and crystallizable fragment (Fc). Fab can specifically recognize tumor associated antigen (TAA) and thus modulate TAA-linked downstream signaling pathways that may lead to inhibition of tumor growth, induction of tumor apoptosis and differentiation. The Fc region can further improve mAbs’ efficacy by mediating effector functions such as antibody-dependent cellular cytotoxicity (ADCC), complement-dependent cytotoxicity (CDC) and antibody dependent cell-mediated phagocytosis (ADCP). Moreover, Fc is the region interacting with the neonatal Fc receptor (FcRn) in a pH-dependent manner that can slow down IgG’s degradation and extend its serum half-life. Loss of the antibody Fc region dramatically shortens its serum half-life and weakens its anti-cancer effects. Given the essential roles that the Fc region plays in the modulation of the efficacy of mAb in cancer treatment, Fc engineering has been extensively studied in the past years. This review focuses on the recent advances in therapeutic Fc engineering that modulates its related effector functions and serum half-life. We also discuss the progress made in aglycosylated mAb development that may substantially reduce cost of manufacture but maintain similar efficacies as conventional glycosylated mAb. Finally, we highlight several Fc engineering based mAbs under clinical trials.